Variability of suberin composition of reproduction cork from Quercus suber throughout industrial processing - Conde, E.; GARCIA-VALLEJO, M. C.; Cadahia, E. (HOLZFORSCHUNG, 1999)
The chemical composition of suberin was studied in cork planks fromthree different trees of Spanish Quercus suber at four different stages of the industrial processing of first transformation: stripping (a), first rest (b), boiling followed by open air rest (c1) and boiling followed by store-room rest (c2). The monomeric composition was determined by gas chromatography/mass spectrometry in the product of depolymerization of the free of extractives cork with sodium methoxide-methanol. The average concentrations of the main monomers were: 1-alkanols (C-20-C-26) 4.17 %; alkanoic acids (C-20-C-26) 5.99 %; alpha, omega-alkanedioic acids (C-16-C-24) 6.20 %; omega-hydroxy-alkanoic acids (C-20-C-26) 29.41 %; erythro- and threo-9, 10-dihydroxyoctadecanedioic acids 6.76 %, erythro- and threo-9,10,18-trihydroxyoctadecanoic acids 9.50 %, 9,10-epoxy-18-hydroxyoctadecanoic acid 2.72 % and 9,10-epoxy-octadecanedioic acid 2.93 % and ferulic acid 5.05 %. Significant differences were observed between samples taken at the stripping and after boiling with store room rest, and both groups of samples differed from those picked after the other two processing stages. Ten components were selected as providing the greatest discrimination among stages: 9-octadecenedioic, 18-hydroxy-9-octadecenoic, eicosanedioic and 9,10-epoxy-18-hydroxy-octadecanoic acids, tetracosanol, and five unidentified components.
The following values have no corresponding Zotero field: pub-location: GENTHINER STRASSE 13, D-10785 BERLIN, GERMANY publisher: WALTER DE GRUYTER & CO
Keywords: Quercus suber; suberin; cork; industrial processin